2020
DOI: 10.1111/dom.14063
|View full text |Cite
|
Sign up to set email alerts
|

Validation of distinct type 2 diabetes clusters and their association with diabetes complications in the DEVOTE, LEADER and SUSTAIN‐6 cardiovascular outcomes trials

Abstract: AimsTo validate the clusters of Swedish individuals with recent‐onset diabetes at differential risk of complications, which were identified in a previous study, in three global populations with long‐standing type 2 diabetes (T2D) who were at high cardiovascular risk, and to test for differences in the risk of major diabetes complications and survival endpoints.Materials and methodsWe assigned participants from recent global outcomes trials (DEVOTE [n = 7637], LEADER [n = 9340] and SUSTAIN‐6 [n = 3297]) to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
91
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(102 citation statements)
references
References 14 publications
7
91
1
3
Order By: Relevance
“…The proportion of the SIRD cluster ranged within 7.2% and 23.7% among studies, while 2 similar clusters were revealed by Safai et al such as insulin resistance with short disease duration (21.4%) and insulin resistance with long disease duration (31.7%) [7][8][9]14,[16][17][18]20]. The next most frequent cluster was MOD with varying percentages between studies from 20.4% to 34% [7][8][9]14,17,18,20]. The MARD cluster was the most prevalent among the mentioned five clusters in each study, falling within 34% and 45.4% [7][8][9]14,17,18,20].…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…The proportion of the SIRD cluster ranged within 7.2% and 23.7% among studies, while 2 similar clusters were revealed by Safai et al such as insulin resistance with short disease duration (21.4%) and insulin resistance with long disease duration (31.7%) [7][8][9]14,[16][17][18]20]. The next most frequent cluster was MOD with varying percentages between studies from 20.4% to 34% [7][8][9]14,17,18,20]. The MARD cluster was the most prevalent among the mentioned five clusters in each study, falling within 34% and 45.4% [7][8][9]14,17,18,20].…”
Section: Resultssupporting
confidence: 67%
“…), and 2 studies were conducted on mice. As a result, 14 papers were found to be eligible: 10 articles were included in the review [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ] and an additional 4 eligible papers were found after hand-searching of the reference lists of selected articles [ 17 , 18 , 19 , 20 ]. The selection process is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations